PENGARUH MOTIVASI, BIAYA PENDIDIKAN DAN LAMA PENDIDIKAN PADA MINAT MAHASISWA AKUNTANSI MENGIKUTI PPAK - Berlinasari, Mayma; Erawati, Adi (E-Jurnal Akuntansi, 2017)
Accounting Profession Education (PPAk) is very important for students majoring in accounting, because PPAk can contribute to being a professional accountant. This study aims to determine the effect of motivation quality, career motivation, economic motivation, education cost and long education on interest accounting student following the accounting profession education (empirical study on accounting students s1 program Faculty of Economics and Business, University Udayana). The sample was 65 respondents to the sampling method used nonprobality sampling with purposive sampling technique. Data collection methods used were questionnaires. Data analysis technique used is multiple linear regression analysis to test the hypothesis. Based on the results of the analysis can be concluded that the motivation variable quality, career motivation and positive influence on economic motivation of student interest in accounting follows the Accounting Profession while variable tuition fees and length of education negatively affect the interests of accounting students to follow Accounting Profession.
Keywords: Quality Motivation, Career Motivation, Economic Motivation, Education Cost, Long Education, Interest Accounting Student Following PPAk